The effectiveness of a mindfulness intervention in reducing anxiety levels among vocational high school students - Indarna, Asep Aep; Widyawati, Widyawati (JOURNAL OF Mental Health Concerns, 2026)
Background: Anxiety is one of the most frequently reported psychological problems among adolescents, particularly among Vocational High School students who are required to meet both academic and career readiness demands. Mindfulness has been widely recognized for its effectiveness in reducing anxiety across various populations; however, empirical studies focusing on Indonesian vocational education settings remain limited. Purpose: To evaluate the effect of mindfulness intervention on anxiety levels among students and to identify variations in effectiveness based on gender and baseline anxiety levels. Method: A quasi-experimental pre-test–post-test design with a control group was employed. Participants were selected through purposive sampling, and anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Statistical analysis was conducted using the Wilcoxon test and Two-Way ANOVA. Results: A significant decrease in anxiety levels was found in the intervention group (p < 0.001), whereas no significant change occurred in the control group. Effectiveness varied according to gender and initial anxiety level. Conclusion: Mindfulness intervention is effective in reducing anxiety among students and may yield greater benefits when tailored to individual characteristics.   Keywords: Adolescents; Anxiety; Mental Health; Mindfulness; Vocational Education.